Comparison of continuous‐flow ventricular assist device therapy with intensive medical therapy in fixed pulmonary hypertension secondary to advanced left heart failure. (24th March 2018) - Kumarasinghe, Gayathri; Jain, Pankaj; Jabbour, Andrew; Lai, Jacqueline; Keogh, Anne M.; Kotlyar, Eugene; Jansz, Paul; Macdonald, Peter S.; Hayward, Christopher S.
Abstract: Aims: Both ventricular assist device (VAD) and pulmonary vasodilator therapy have been shown in uncontrolled studies to improve pulmonary hypertension secondary to advanced left heart failure (Group 2 PH). This study aimed to compare haemodynamic benefits and survival in patients with fixed Group 2 PH treated with continuous‐flow VAD to intensive medical therapy. Methods and results: Ninety‐five patients listed for heart transplantation with sequential right heart catheters were studied, 24 patients having fixed Group 2 PH (as defined by cardiac index < 2.8 L/min/m 2, pulmonary capillary wedge pressure > 15 mmHg, and transpulmonary gradient ≥ 15 mmHg or pulmonary vascular resistance > 3.0 WU, unresponsive to vasodilator challenge). Ten patients received VAD therapy, and 14 patients received standard heart failure therapy with or without sildenafil, nitrates, or endothelin receptor antagonists. At repeat right heart catheterization, patients treated with VAD therapy demonstrated significant improvement in both transpulmonary gradient (19 vs. 12 mmHg, P  = 0.046) and pulmonary vascular resistance (6.5 vs. 2.9 WU, P  = 0.003) compared with baseline, while those treated with medical therapy did not (20.9 vs. 20.3 mmHg and 6.5 vs. 6.4 WU, P  = NS for both). Patients who received VAD therapy were significantly more likely to achieve normalized transpulmonary gradient (8/10 vs. 4/14, P  = 0.013) and were more likely to be listed for orthotopic heart transplantation (7/10 vs. 4/14, P  < 0.05). There were no significant differences between groups in terms of all‐cause mortality. Conclusions: Continuous‐flow VAD therapy more effectively reverses fixed Group 2 PH compared with medical therapy alone and may allow a higher rate of listing for orthotopic heart transplantation.